2016
DOI: 10.1007/s00330-016-4666-y
|View full text |Cite
|
Sign up to set email alerts
|

Tip malposition of peripherally inserted central catheters: a prospective randomized controlled trial to compare bedside insertion to fluoroscopically guided placement

Abstract: • Bedside and fluoroscopy guided techniques are commonly used for PICC placement. • Catheter malposition is the major technical issue with the bedside technique. • Catheter malposition occurred in 53% of patients with the bedside technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 25 publications
2
56
1
1
Order By: Relevance
“…The malposition of the catheter tip may occur at the time of insertion or later on as a result of spontaneous migration due to anatomic positioning or pressure changes within the thoracic cavity [18,19]. The malposition rate is known to be between 1.8%-9.3% for non-PICC type CVCs [20,21] and 10% and 53% for PICCs [8,9]. In our study, malposition on the initial chest radiograph was found in 110 cases (8.5%).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The malposition of the catheter tip may occur at the time of insertion or later on as a result of spontaneous migration due to anatomic positioning or pressure changes within the thoracic cavity [18,19]. The malposition rate is known to be between 1.8%-9.3% for non-PICC type CVCs [20,21] and 10% and 53% for PICCs [8,9]. In our study, malposition on the initial chest radiograph was found in 110 cases (8.5%).…”
Section: Discussionmentioning
confidence: 55%
“…Complications include catheter malposition, migration, occlusion, infection, and venous thrombosis [5,7]. Amidst these complications, the occurrence of catheter malposition increases when PICC placement is performed as a bedside procedure without fluoroscopic guidance [8]. The estimated rate of tip malposition with bedside PICCs varies between 10% and 53% [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transthoracic echocardiography has been suggested to determine catheter tip position, but randomized, controlled trials (RCT) have not been published and expertise with the technique and equipment is not widely available . The frequency of unsuccessful and complicated insertions without imaging (eg, at the bedside) remains unacceptably high and should not be routinely attempted in high‐risk patients . Collaboration between vascular access nurses and interventional radiologists may offer improved outcomes compared with bedside insertion …”
Section: Failure Points and Essential Components Of Carementioning
confidence: 99%
“…64,65 The frequency of unsuccessful and complicated insertions without imaging (eg, at the bedside) remains unacceptably high and should not be routinely attempted in high-risk patients. 66,67 Collaboration between vascular access nurses and interventional radiologists may offer improved outcomes compared with bedside insertion. 68 Emergent and urgent devices (ie, "temporary catheters") placed without maximum sterile barrier precautions, or catheters with tips positioned at a distance from the cavoatrial junction, should be removed as soon as possible after stabilization of the patient.…”
Section: Elective Access Conditionsmentioning
confidence: 99%